2007
DOI: 10.1080/13697130701463594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three doses of conjugated estrogens/medroxyprogesterone acetate on biomarkers of bone turnover and cartilage degradation in postmenopausal women: The Pan-Asia Menopause (PAM) study

Abstract: Lowering the commonly used dose of 0.625 mg CE + 2.5 mg MPA to 0.45 mg CE + 1.5 mg MPA does not significantly alter the inhibitory effect on bone and cartilage turnover in Asian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Interestingly, a significant correlation between baseline biomarkers and baseline estradiol levels, reported earlier 28 , was also apparent. The correlation was weak but statistically significant; it is noteworthy that it was negative and thus consistent with the biomarker-lowering effect of exogenous HT that we previously showed in this population 23 . Interestingly, in pre-and early perimenopausal women of the Study of Women's Health Across the Nation (SWAN), there was no significant association between the bone turnover markers osteocalcin and urinary N-telopeptide of type I collagen (NTx) compared to endogenous estradiol, a difference that may in part be due to the different menopausal status of women in the two studies 30 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, a significant correlation between baseline biomarkers and baseline estradiol levels, reported earlier 28 , was also apparent. The correlation was weak but statistically significant; it is noteworthy that it was negative and thus consistent with the biomarker-lowering effect of exogenous HT that we previously showed in this population 23 . Interestingly, in pre-and early perimenopausal women of the Study of Women's Health Across the Nation (SWAN), there was no significant association between the bone turnover markers osteocalcin and urinary N-telopeptide of type I collagen (NTx) compared to endogenous estradiol, a difference that may in part be due to the different menopausal status of women in the two studies 30 .…”
Section: Discussionsupporting
confidence: 87%
“…As part of the PAM study, we have recently reported responsiveness of bone and cartilage biomarkers to conjugated estrogens/ medroxyprogesteone acetate (CE/MPA) therapy in the overall study population 23 . The present Our study was conducted at large academic and clinical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible dose-response effect on bone mass was revealed in Chinese women. In a Pan-Asian study, markers of bone turnover were reduced by three doses of CEE/MPA 0.625/2.5, 0.45/1.5, 0.3/1.5 mg in postmenopausal Asian women after 6-month treatment, and the effects were strongest with the 0.625/2.5 mg dose and weakest with the 0.3/1.5 mg dose 48 . The BMD at the lumbar spine was increased by 4.16% vs. 1.51% in postmenopausal women after 12 months of treatment with transdermal estradiol 50 mg vs. 25 mg 33 .…”
Section: Effects Of Low-dose Hormone Therapy On Bonementioning
confidence: 97%